2009
DOI: 10.1093/nar/gkp380
|View full text |Cite
|
Sign up to set email alerts
|

Physical and functional interactions between Escherichia coli MutL and the Vsr repair endonuclease

Abstract: DNA mismatch repair (MMR) and very-short patch (VSP) repair are two pathways involved in the repair of T:G mismatches. To learn about competition and cooperation between these two repair pathways, we analyzed the physical and functional interaction between MutL and Vsr using biophysical and biochemical methods. Analytical ultracentrifugation reveals a nucleotide-dependent interaction between Vsr and the N-terminal domain of MutL. Using chemical crosslinking, we mapped the interaction site of MutL for Vsr to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…This would have the overall effect of creating a shorter repair track. In addition, this would be consistent with previously reported results, indicating that MutL interacts with the Vsr endonuclease and stimulates the binding of this protein to its substrate (24,32,45,46).…”
Section: Because Of This Confounding Ligation Product We Measured LIsupporting
confidence: 93%
See 4 more Smart Citations
“…This would have the overall effect of creating a shorter repair track. In addition, this would be consistent with previously reported results, indicating that MutL interacts with the Vsr endonuclease and stimulates the binding of this protein to its substrate (24,32,45,46).…”
Section: Because Of This Confounding Ligation Product We Measured LIsupporting
confidence: 93%
“…Therefore, MutS and MutL must have some role in the VSP repair pathway, such that these proteins increase the efficiency of VSP repair. Previous results (24,32) have shown that MutL interacts with the Vsr endonuclease and apparently stimulates binding to the DNA substrate. We have confirmed this result that, in our hands, is only apparent at high concentrations of MutL (data not shown).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations